Business logic: The missing link between strategy, business model and business process? - Jon Williamsson; Anders Sandoff; Gabriela Schaad (Journal of Business Models (JOBM), 2019)
Like military strategists, business professionals orient themselves in the world supported by an overarching, yet by researchers unlabeled, understanding of how different organizational levels develop and interact. Researchers may understand this phenomenon by utilizing the idea of military doctrine and introducing a similar concept tentatively called business logic .
Keywords: 650; Business model; military doctrine; business logic